HOUSEHOLD LIVELIHOOD DEVELOPMENT OF THE H’MONG IN ROMEN COMMUNE, DAMRONG DISTRICT, LAMDONG PROVINCE - Phạm Hồng Hải (Tạp chí Khoa học Đại học Đà Lạt)
This paper analyzes the funds used to ensure the livelihoods and clarifies the status of livelihood activities of the H’Mong in Romen commune. The research results show clearly that the livelihood resources of H’Mong households in Romen commune have been improved, especially natural capital and physical capital. Besides the main livelihood of crop cultivation, other livelihood activities such as trade and raising livestock are gradually forming and starting to grow. However, the financial and human capital of H’Mong households is still inadequate. From the research results, the article recommends some solutions for sustainable livelihood development for the H’Mong people in the future.